Assistance in Developing Market Economics Teaching Modules for Teachers at the Indonesian School Davao, Philippines - Sulistyowati, Raya; Nuswantara, Dian Anita; Indriastuti, Herning; Setyawati, Amelia; Sugangga, Rayyan; Sugangga, Amelia; Rahman, Iradah; Sudarjo; Dirgantari, Puspo Dewi; Zukhruf, Ratu Dintha Insyani; Banu, Syahar (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2024)
This international community service program aims to enhance teachers' skills in developing market economics teaching modules at the Indonesian School in Davao, Philippines. The program includes a series of workshops and intensive mentoring sessions for teachers, focusing on developing market economics teaching materials that align with the curriculum and local context. The approach involves problem identification, preparation, and coordination, activity socialization, implementation through online and offline mentoring, group discussions, and ongoing evaluation to ensure that the knowledge and skills acquired can be effectively applied. The program results significantly improve teachers' ability to design innovative and relevant teaching modules and an increased understanding of market economics concepts. Other positive impacts include establishing a more robust collaborative network between educators in both countries and enhancing the quality of economics education at the Indonesian School in Davao, Philippines. The program has successfully created a more interactive and engaging learning environment for students.